Political Marketing in Morocco: From Theories to Stereotypes, Definition and Comparison - Makry, Hajar; Berbou, Houcine; Oulhadj, Badia (International Review of Management and Marketing, 2019)
At a time when Moroccan researchers still undecided on the appropriate definition of Political Marketing, the debate around this subject is initiated already, whether on their side the opinion makers, the media and the politicians themselves. Among supporters and opponents of the adoption and the use of this discipline's strategies, each one according to his own definition of Political Marketing, few months before 2016's elections in Morocco, the debate around this emerging science, is growing increasingly. Through an exploratory survey, we tried to highlight the common perception in analytical comparison, with what was overdraft, until today by international research. The purpose is an essay of definition adapted to the needs of this particular Moroccan context. Considering that rare are the academic researches that has been initiated in Morocco, around the concept, this paper is an analysis of the gap, among common perception, and scientific conceptual framework of this discipline. Keywords: Marketing, Political Marketing in Morocco, Political actors. JEL Classifications: M31, D83, M10 DOI: https://doi.org/10.32479/irmm.8110